KAJIAN ETNOBIOLOGI UPACARA ADAT DI DESA WORAT-WORAT KECAMATAN SAHU, KABUPATEN HALMAHERA BARAT - Eva Uny; Euis S. Pangemanan; Reynold P. Kainde (COCOS, 2018)
ABSTRACT The Worat-Worat Village community still uses plants in their daily lives as medicines, household appliances, wicker, clothing, food, shelter, and traditional ceremonies. Traditional ceremonies in Woratworat village which are still used today are: traditional eating ceremonies (Orom Sasadu) and traditional wedding ceremonies. This study aims to determine the types and benefits of plants and animals at a traditional ceremony in Worat-worat Village, Sahu District, West Halmahera Regency. The method used in the study was interviews and field observations. The technique of selecting informants using purposive sampling technique. Informants were chosen with certain considerations, in this case the informants chosen to be interviewed were traditional leaders, village leaders and the community. The results showed that plants and animals used in traditional ceremonies included 18 types of plants, namely: rice, sugar palm, betel, areca nut, banana forest, gofasa, sago, cempaka, yellow bamboo, bamboo stone, talang bamboo, balsam tree, durian, melinjo , rattan, kayu besi, coconut and langsat and 4 types of animals namely: wild boar, deer, gosong kelam, and rice snail. The use of plant and animal species in traditional ceremonies is very diverse. The use of these plants starts from the stem, bark, leaves, fruit, and sap. While the animal parts that are utilized are: rice conch shells are used as lime meal, dusky megapode eggs are used as food, wild boar is used as food and deerskin is used for making tifa. Keywords: Ethnobiology, traditional ceremony, Worat-worat Village